ANALISIS DAN PERANCANGAN SISTEM INFORMASI ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT(e-CRM) PT. DELTA JAYA MOTOR SINGKAWANG - M Qadafi Khairuzzaman (Jurnal Khatulistiwa Informatika, 2016)
PT.Delta Jaya Motor is a company engaged in the sale of spare parts yamaha motor that serves the needs of consumers in large enough quantities. PT.Delta Jaya Motor to retain customers and gain new customers with a wide range of strategies used. The strategy is meant here is the strategy of CRM (Customer Relationship Management ) which is one of the tools of collaboration with customers who use a variety of companies to maintain the relationship and create a situation of win-win by improving the value of customers' lives every day through a variety of ways , so that the customer remain loyal to the services provided by these companies. So customer satisfaction will be measured by the success of product marketing. Design and analysis methods used in the development Electronic Customer Relationship Management (E-CRM) is the system Linear Sequential atau Waterfall Model. This method is a classical model which is systematic and easy to understand because the successive stages of building a software ranging from process communication, planning, modeling, construction hingga proses deployment.